Visual Consciousness System Model in Chinese Drama - Fachri Helmanto; Arif Hidayat; Deden Haerudin (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
Chinese dramas on short-video platforms reorganize narrative logic by introducing a visual system immediately after moments of crisis. This host-exclusive interface assigns missions, rewards, and procedural actions, shifting storytelling from exploratory problem-solving to system-driven intervention that directly bypasses narrative obstacles. This study employs a qualitative approach using document-based structural narrative analysis. Narrative readings are conducted through Chase?s narrative model to examine how systems function as meaning-making practices within Chinese digital dramas. Narrative is conceptualized as a cultural mechanism that organizes crisis and problem-solving through visual systems. The data consist of digital narrative documents, including selected episode segments, crisis scenes, and visual system representations from dramas themed around reincarnation and cross-reality transitions. The analysis applies thematic procedures to map system functions in structuring relations between crisis, action, and outcomes. The findings formulate a Visual Consciousness System Model that explains how narrative crises trigger system activation, transforming the protagonist into a host-exclusive subject governed by predefined system parameters. Within this model, crisis functions as an activation threshold, the system operates as a host-only interface, and character consciousness is procedurally oriented toward task execution rather than reflective evaluation. Action unfolds through system-regulated procedures, producing outcomes that resolve crisis without narrative exploration and reproduce new crisis conditions through continued system dependence. This model implies a broader shift in digital storytelling, where problem-solving is no longer framed as cognitive exploration but as procedural compliance with visual systems. Narrative agency is reconfigured as system alignment, and creativity is reduced to optimization within closed parameters rather than the generation of alternative narrative possibilities.